PENGEMBANGAN MODEL PEMBELAJARAN DAN MINAT MELALUI PERMAINAN SOBASE (SOFTBALL-BASKET-SEPAKBOLA) PADA SISWA SMA NEGERI 1 CEPOGO TAHUN 2021 - Hargiyana, Aditya (Universitas Negeri Semarang, 2021)
The purpose of this study was to describe the form of the SOBASE game in physical education learning for students at SMA Negeri 1 Cepogo and to find out how interested students are inparticipating in this SOBASE game. The type of this study was development research. Thesubjects of this study trial were students of SMA Negeri 1 Cepogo as many as 20 students in thesmall-scale trial and 60 students in the large-scale trial. The data collection technique usedquestionnaires and documentation. The data analysis technique used in this study was apercentage descriptive analysis technique, while the validation was analyzed using descriptiveanalysis. The results of small-scale trials expert evaluation data showed, from the first gamedeveloper expert averaged 95.3% and the second game developer expert averaged 93.75%, theresults of small-scale trials 20 students had a high category interest. The results of the largescale trial of expert evaluation data showed, from the first game developer expert averaged100% and the second game developer expert 100%, the results of the large-scale trial were 57students had a high category interest and 3 students were in the medium category.